Quality of Work Culture and Employees' Satisfaction - Bhatt , Padam Raj (The Management Review, 2026)
This research article examines the complicated relationship between work culture and employee satisfaction within the context of the Nepalese banking sector, with a specific focus on Sudurpaschim province, Kanchanpur Mahendranagar. The findings disclose main aspects of work culture, employee satisfaction, and factors influencing both. The study contributes valuable insights to the ongoing discourse on the banking industry’s challenges and prospects in Nepal. The research has found the factors contributing to the quality of work culture (QWC) in Nepalese banks and proposes strategies for improving work culture to encourage employee satisfaction, commitment, and loyalty. The study appraises work culture variables, their effect on employee satisfaction, and the correlation between them. Research inquiries look into work culture variables, their effects on employee satisfaction, and potential correlations. Hypotheses evaluate the significance of the association between work culture and employee satisfaction, including the impact of demographic variables. The significance of is in its contribution to considerate the dynamics of work culture and employee satisfaction in the evolving Nepalese banking industry. The conclusions, based on a comprehensive survey of 29 bank branches in Mahendranagar, offer insights into management practices, employee perception, and areas for improvement. The study concludes with practical recommendations and implications for policymakers, organizational leaders, and future research directions.